A computational framework for meso and macroscale analysis of structural masonry. (1st February 2022) - Koocheki, K.; Pietruszczak, S.; Haghighat, E.
Abstract: In this study a computational framework is outlined for modeling the mechanical response of structural masonry at both meso and macroscale. The mesoscale approach accounts for the presence of distinct constituents (i.e., bricks and mortar joints) and their geometric arrangement. A constitutive law with embedded discontinuity, combined with the level-set approach, is used to model the onset and discrete propagation of localized damage in these constituents. The approach is verified against a range of experimental data published in the literature. It is shown that the proposed framework can adequately predict the load-deformation response, as well as the fracture pattern under combined loading conditions. The macroscale approach incorporates the notion of anisotropy parameter whose value depends on the orientation of the principal stress axes in relation to the axes of material symmetry. The material parameters/function appearing in this approach are identified from the 'virtual data' generated by a mesoscale analysis of masonry panels subjected to biaxial tension–compression at different orientations of the bed joint. Thus, the mesoscale considerations serve as a bridge for upscaling to the macrolevel.